Unusual congenital goiter due to maternal Hashimoto thyroiditis: a case report - Laura Català; Judit Casas; Sean Yeh; Maria Josa-Eritja; Maria Josa-Eritja; Maria Josa-Eritja; Mireia Tirado-Capistros; Mireia Tirado-Capistros; Mireia Tirado-Capistros; Elisenda Moliner; Elisenda Moliner; Elisenda Moliner; et al. (Frontiers Media S.A., 2024)
Congenital hypothyroidism (CH) is the most common cause of endocrinopathy in the newborn Its incidence lies between 1 in 3,000 and 1 in 2,000, However, congenital goiter is a rare form of presentation. Hypothyroidism secondary to autoimmune etiology is extremely rare, with an incidence of 1:84.700-1:31.000 newborns. Anti-thyroid peroxidase antibodies (TPOAb) are able to cross the placenta but rarely induce hypothyroidism in the newborn, much less goiter. A case of congenital goiter in a male newborn secondary to maternal high TPOAb levels is reported. The mother was diagnosed of Hashimoto thyroiditis prior to the pregnancy. At birth, a grade 3 goiter was detected in the newborn. Laboratory testings revealed hypothyroidism with free thyroxine of 7.6 pmol/L, thyroid-stimulating hormone of 108 mUI/L and high TPOAb levels. Treatment with Levothyroxine was started the second day of life with progressive thyroid function normalization. Neurological development has been normal until the date.